Modulation of the cyclic AMP content of rat renal inner medulla by oxygen: possible role of local prostaglandins. - DeRubertis, F R (1976)
The lower O2 tension and more active anerobic metabolism that pertain in the inner medulla (IM) of kidney relative to cortex (C) are well recognized, but there is no evidence that O2 availability constitutes a limiting or regulatory factor in IM metabolism or function. In the present in vitro study, we examined the effects of O2 on adenosine 3',5'-monophosphate (cAMP) metabolism in slices of rat renal C and IM. After a 20-min incubation of slices in Krebs Ringer bicarbonate buffer with 95% O2 + 5% CO2 serving as the gas phase, the cAMP content of IM was 6-10 fold higher than that of C in either the presence or absence of 2 mM 1-methyl-3-isobutylxanthine in the incubation media. In slices of IM incubated for 20 min with 1-methyl-3-isobutylxanthine, cAMP was 22.5+/-SE 2.48 pmol/mg wet weight at 95% O2 and 4.37 without O2. Oxygenation of O2-deprived IM increased cAMP twofold in 2 min, an effect fully expressed in 5 min (fivefold increase). Further, cAMP of IM rose progressively and significantly over a range of atmospheric O2 content from 0 to 50% conditions which should reproduce and encompass O2 tensions that pertain in tissues in vivo. By contrast, basal cAMP content of C varied less than twofold in the presence of 95% versus no O2, implying that O2 modulation of cAMP was specific for IM. Indomethacin and meclofenamate, structurally distinct inhibitors of prostaglandin synthesis, both significantly decreased basal cAMP accumulation in oxygenated slices of IM but not of C. Meclofenamate also reduced basal adenylate cyclase activity determined in homogenates prepared from slices of IM which had been incubated at 95% O2. In slices of IM previously exposed to indomethacin or meclofenamate at 95% O2, a maximally effective concentration of exogenous prostaglandin E1 restored cAMP and adenylate cyclase activity to levels which approximated those observed at 95% O2 in the absence of an inhibitor of prostaglandin synthesis. These results suggest that O2 enhancement of cAMP content in IM may be mediated at least in part by local prostaglandins.